2016
DOI: 10.1155/2016/7162160
|View full text |Cite
|
Sign up to set email alerts
|

Human Cord Blood‐Derived CD133+/C‐Kit+/Lin Cells Have Bipotential Ability to Differentiate into Mesenchymal Stem Cells and Outgrowth Endothelial Cells

Abstract: Recent evidence suggests that mononuclear cells (MNCs) derived from bone marrow and cord blood can differentiate into mesenchymal stem cells (MSCs) or outgrowth endothelial cells (OECs). However, controversy exists as to whether MNCs have the pluripotent capacity to differentiate into MSCs or OECs or are a mixture of cell lineage-determined progenitors of MSCs or OECs. Here, using CD133+/C-kit+/Lin− mononuclear cells (CKL− cells) isolated from human umbilical cord blood using magnetic cell sorting, we characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
2
7
0
Order By: Relevance
“…Indeed, CD34 + c-Kit + populations have already been c-Kit − cells among the CD34 + CD45 dim CD133 + population. g Illustration of CD45 and CD133 expressions according distinct patterns for CD34 and KDR of live lineage negative cells in peripheral blood of COVID-19 patients -Among the live cells, each of the 4 populations based on respective expressions of CD34 and KDR are phenotype on the CD45 and CD133 markers thus illustrating that all the KDR + events are exclusively CD45 high CD133 -*p < 0.05; **p < 0.01. described to have endothelial differentiation potential in vivo [20] and CD133 + c-Kit + lin − cells from human cord blood have also already been described to have ability to differentiate in ECFCs [21]. Potential mobilization of these cells in critical COVID-19 could provide endothelial regeneration helpful during hypoxia observed in COVID-19 patients [22,23], but on the other hand could participate to dissemination of thrombotic profile observed in clinic [8].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, CD34 + c-Kit + populations have already been c-Kit − cells among the CD34 + CD45 dim CD133 + population. g Illustration of CD45 and CD133 expressions according distinct patterns for CD34 and KDR of live lineage negative cells in peripheral blood of COVID-19 patients -Among the live cells, each of the 4 populations based on respective expressions of CD34 and KDR are phenotype on the CD45 and CD133 markers thus illustrating that all the KDR + events are exclusively CD45 high CD133 -*p < 0.05; **p < 0.01. described to have endothelial differentiation potential in vivo [20] and CD133 + c-Kit + lin − cells from human cord blood have also already been described to have ability to differentiate in ECFCs [21]. Potential mobilization of these cells in critical COVID-19 could provide endothelial regeneration helpful during hypoxia observed in COVID-19 patients [22,23], but on the other hand could participate to dissemination of thrombotic profile observed in clinic [8].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study showed that cord blood-derived mononuclear cells (MNCs) can differentiate into MSCs or outgrowth endothelial cells (OECs) [11]. We also characterized the differentiation potential of CD133 + /Ckit + /Lin − MNCs (CKL − cells) isolated from human umbilical cord blood (UCB) and confirmed that CKL − cells spontaneously differentiate into MSCs or OECs by performing RT-PCR and immunofluorescence staining for the respective specific markers [11].…”
Section: Backgroundsmentioning
confidence: 66%
“…Our previous study showed that cord blood-derived mononuclear cells (MNCs) can differentiate into MSCs or outgrowth endothelial cells (OECs) [11]. We also characterized the differentiation potential of CD133 + /Ckit + /Lin − MNCs (CKL − cells) isolated from human umbilical cord blood (UCB) and confirmed that CKL − cells spontaneously differentiate into MSCs or OECs by performing RT-PCR and immunofluorescence staining for the respective specific markers [11]. Based on the reported beneficial effects of human MSCs against sepsis [9,10], we hypothesized that human umbilical cord blood-derived mesenchymal stem cells (hUCB-MSCs) could alleviate sepsis-associated acute organ and systemic inflammation via their immunomodulatory properties to improve survival in LPS-induced sepsis.…”
Section: Backgroundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were fixed in 4% formaldehyde, dehydrated in an ethanol series, and embedded in paraffin blocks. Blocks were cut, and sections were stained for sulphated proteoglycans with Safranin O (0.1% aqueous solution) (Sigma-Aldrich) to evaluate chondrogenic differentiation [43,44].…”
Section: Flow Cytometric Analysismentioning
confidence: 99%